Laparoscopic repair of giant paraesophageal hernia with synthetic mesh: 45 consecutive cases. - Stavropoulos, George; Flessas, Ioannis I; Mariolis-Sapsakos, Theodoros; Zagouri, Flora; Theodoropoulos, George; Toutouzas, Konstantinos; Michalopoulos, Nikolaos V; Triantafyllopoulou, Ioanna; Tsamis, Dimitrios; Spyropoulos, Basilios G; Zografos, George C (Am Surg, 2012)
Giant paraesophageal hernias (PEHs) are associated with progression of symptoms in up to 45 per cent of patients. Recently, many series have reported that laparoscopic repair of PEH is technically feasible, effective, and safe. A retrospective review of the University of Athens tertiary care hospitals patient database and the patient medical records identified 45 patients who underwent elective repair of a giant PEH between 2002 and 2009. Elective laparoscopic repair of a giant PEH was attempted in 45 patients who were treated with Gore-Tex dual mesh with or without Nissen fundoplication. They all had a mesh repair. Intraoperative complications included one pulmonary embolism and one recurrent hernia. The use of a mesh seems to be effective in the treatment of large hernias. It appears to offer the benefit of a shorter hospital stay and a quicker recovery.
Keywords: Elective Surgical Procedures; Follow-Up Studies; Fundoplication; Hernia, Hiatal; Herniorrhaphy; Humans; Laparoscopy; Retrospective Studies; Surgical Mesh; Treatment Outcome